Unconventional EGF-induced ERK1/2-mediated Kv1.3 endocytosis - Martínez-Mármol, Ramón (Cell Mol Life Sci, 2015)
The potassium channel Kv1.3 plays roles in immunity, neuronal development and sensory discrimination. Regulation of Kv1.3 by kinase signaling has been studied. In this context, EGF binds to specific receptors (EGFR) and triggers tyrosine kinase-dependent signaling, which down-regulates Kv1.3 currents. We show that Kv1.3 undergoes EGF-dependent endocytosis. This EGF-mediated mechanism is relevant because is involved in adult neural stem cell fate determination. We demonstrated that changes in Kv1.3 subcellular distribution upon EGFR activation were due to Kv1.3 clathrin-dependent endocytosis, which targets the Kv1.3 channels to the lysosomal degradative pathway. Interestingly, our results further revealed that relevant tyrosines and other interacting motifs, such as PDZ and SH3 domains, were not involved in the EGF-dependent Kv1.3 internalization. However, a new, and yet undescribed mechanism, of ERK1/2-mediated threonine phosphorylation is crucial for the EGF-mediated Kv1.3 endocytosis. Our results demonstrate that EGF triggers the down-regulation of Kv1.3 activity and its expression at the cell surface, which is important for the development and migration of adult neural progenitors. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00018-015-2082-0) contains supplementary material, which is available to authorized users.